2018
DOI: 10.1002/ceas.12108
|View full text |Cite
|
Sign up to set email alerts
|

Telling of Institutional Oppression: Voices of Minoritized Counselor Educators

Abstract: The authors use the results of an intersectional critical qualitative inquiry to illustrate the encounters 6 minoritized counselor educators had with institutional forms of oppression. Their findings depict the insidious nature of institutional oppression and suggest that counselor educator experiences may be improved by peer mentorship programs and by the organizational advocacy and accountability efforts of bodies such as the Association for Counselor Education and Supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
(47 reference statements)
2
27
0
Order By: Relevance
“…Adverse experiences were commonly reported as exemplifying different types of microaggressions, which are "brief and commonplace daily verbal, nonverbal, and environmental slights, insults, invalidations, and indignities, whether they are intentional or unintentional, which are directed toward [marginalized individuals]" (Sue et al, 2007, p. 271). Across studies, participants reported experiencing microaggressions throughout interactions with peers and faculty members (Baker & Moore, 2015;Bryan, 2018;Cartwright et al, 2018;Casado Pérez & Carney, 2018;Haskins et al, 2016;Henfield et al, 2011;Pollock & Meek, 2016;Shillingford et al, 2013;Speciale et al, 2015). These experiences were often presented as overt microaggressions.…”
Section: Overt Microaggressionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adverse experiences were commonly reported as exemplifying different types of microaggressions, which are "brief and commonplace daily verbal, nonverbal, and environmental slights, insults, invalidations, and indignities, whether they are intentional or unintentional, which are directed toward [marginalized individuals]" (Sue et al, 2007, p. 271). Across studies, participants reported experiencing microaggressions throughout interactions with peers and faculty members (Baker & Moore, 2015;Bryan, 2018;Cartwright et al, 2018;Casado Pérez & Carney, 2018;Haskins et al, 2016;Henfield et al, 2011;Pollock & Meek, 2016;Shillingford et al, 2013;Speciale et al, 2015). These experiences were often presented as overt microaggressions.…”
Section: Overt Microaggressionsmentioning
confidence: 99%
“…For example, a Black student reported feeling judged based on his casual dress style, which was stereotypically indicative of hip-hop culture. Faculty members of color also commonly reported that racial stereotypes infiltrate their interactions during the job search process, in classrooms with students, and between colleagues (Cartwright et al, 2018;Casado Pérez & Carney, 2018;Hill et al, 2005;Shillingford et al, 2013).…”
Section: Stereotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversity and inclusion research about counselor educators included quantitative investigation of mothers’ occupational satisfaction (Neale‐McFall, Eckart, Hermann, Haskins, & Ziomek‐Daigle, 2018). Qualitative inquiries included experiences of “minoritized” (Pérez & Carney, 2018, p. 162) faculty members with institutional oppression and campus interviews (Cartwright, Avent‐Harris, Munsey, & Lloyd‐Hazlett, 2018), as well as analyses of African American male counselors’ social justice efforts (Dollarhide et al, 2018) and actions of LGBTQ+ competent faculty members (Gess & Doughty Horn, 2018).…”
Section: Understanding Stakeholdersmentioning
confidence: 99%
“…Counselors aiming to heal a “legacy of silence” (Day‐Vines et al, 2007, p. 402) in relation to identity and power in the status quo can do so by broaching or inviting explicit dialogue with clients about race, ethnicity, and culture. Scholars have suggested that broaching can help remove barriers to accessing mental health services for minoritized clients (a term that exposes “the socially constructed nature of underrepresentation and disadvantage”; Harper, 2012, cited in Pérez & Carney, 2018, p. 162), thus offsetting disproportionately high attrition rates (Cardemil & Battle, 2003; Jones & Welfare, 2017). In many ways, broaching translates abstract competencies such as the Multicultural and Social Justice Counseling Competencies (MSJCC; Ratts, Singh, Nassar‐McMillan, Butler, & McCullough, 2015) into an actionable skill—an attractive and practical development that counselor trainees and counselor educators have been clamoring for (Alberta & Wood, 2009; Collins, Arthur, Brown, & Kennedy, 2015).…”
Section: Operationalized Broaching Conditionsmentioning
confidence: 99%